2019
DOI: 10.5194/tc-2019-157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sea ice export through the Fram Strait derived from a combined model and satellite data set

Abstract: Abstract. Sea ice volume export through the Fram Strait plays an important role on the Arctic freshwater and energy redistribution. The combined model and satellite thickness (CMST) data set assimilates CryoSat-2 and Soil Moisture and Ocean Salinity (SMOS) thickness products together with satellite sea ice concentration. The CMST data set closes the gap of stand-alone satellite-derived sea ice thickness in summer and therefore allows us to estimate sea ice volume export during the melt season. In this study, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The FESOM control run well represents the declining trend and interannual variability of both Arctic sea ice volume and summer sea ice extent as depicted by the comparison with PIOMAS result and satellite observations in Figures 1a and 1b. The spatial patterns of sea ice thickness (with thicker sea ice north of Greenland and CAA and thinner sea ice toward the Eurasian coast) and sea ice drift (with anticyclonic circulation in the Canada Basin and the TDS toward Fram Strait) shown in Figure 1c are consistent with observations and reanalysis (Kwok, 2018; Min et al., 2019). The magnitudes of the drift speed are similar to those in CMST (Min et al., 2019).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The FESOM control run well represents the declining trend and interannual variability of both Arctic sea ice volume and summer sea ice extent as depicted by the comparison with PIOMAS result and satellite observations in Figures 1a and 1b. The spatial patterns of sea ice thickness (with thicker sea ice north of Greenland and CAA and thinner sea ice toward the Eurasian coast) and sea ice drift (with anticyclonic circulation in the Canada Basin and the TDS toward Fram Strait) shown in Figure 1c are consistent with observations and reanalysis (Kwok, 2018; Min et al., 2019). The magnitudes of the drift speed are similar to those in CMST (Min et al., 2019).…”
Section: Resultssupporting
confidence: 84%
“…The spatial patterns of sea ice thickness (with thicker sea ice north of Greenland and CAA and thinner sea ice toward the Eurasian coast) and sea ice drift (with anticyclonic circulation in the Canada Basin and the TDS toward Fram Strait) shown in Figure 1c are consistent with observations and reanalysis (Kwok, 2018; Min et al., 2019). The magnitudes of the drift speed are similar to those in CMST (Min et al., 2019). In particular, in Fram Strait, sea ice drift closely follows the satellite observation and the CMST result on the monthly time scale (Figure 2a).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The CMST thickness data cover both the cold seasons and the melting seasons for the period of October 2010 to December 2016 on an 18-km grid. The CMST has been already quantitatively evaluated against observations by a previous study (Min et al, 2019;Mu et al, 2018), demonstrating an accurate performance in simulating the real sea ice drift and thickness. To reduce the noise in ice drift fields and hence divergence calculation, we follow Holland and Kimura (2016) and smooth ice drifts with a 400×400 km square-window filter.…”
Section: Methodsmentioning
confidence: 90%
“…Compared with the average from 2010 to 2016, an additional 233 km 3 of multiyear sea ice were exported through Fram Strait during the season of ice advance in 2011. Although the data used are different, previous studies have also shown an abnormal increase in sea ice fluxes through the Fram Strait in 2011 (Min et al, 2019;Ricker et al, 2018). Hence, multiyear sea ice loss for the season of sea ice advance has contributed to the negative summer sea ice thickness anomalies.…”
Section: Dynamic Transportation Of the Sea Ice Anomalymentioning
confidence: 94%